Impaired in vivo mitochondrial function but similar intramyocellular lipid content in patients with type 2 diabetes mellitus and BMI-matched control subjects - Schrauwen-Hinderling, V. B.; Kooi, M. E.; Hesselink, M. K. C.; Jeneson, J. A. L.; Backes, W. H.; van Echteld, C. J. A.; van Engelshoven, J. M. A.; Mensink, M.; Schrauwen, P. (Diabetologia, 2007)
Mitochondrial dysfunction and increased intramyocellular lipid (IMCL) content have both been implicated in the development of insulin resistance and type 2 diabetes mellitus, but the relative contributions of these two factors in the aetiology of diabetes are unknown. As obesity is an independent determinant of IMCL content, we examined mitochondrial function and IMCL content in overweight type 2 diabetes patients and BMI-matched normoglycaemic controls. In 12 overweight type 2 diabetes patients and nine controls with similar BMI (29.4 +/- 1 and 29.3 +/- 0.9 kg/m(2) respectively) in vivo mitochondrial function was determined by measuring phosphocreatine recovery half-time (PCr half-time) immediately after exercise, using phosphorus-31 magnetic resonance spectroscopy. IMCL content was determined by proton magnetic resonance spectroscopic imaging and insulin sensitivity was measured with a hyperinsulinaemic-euglycaemic clamp. The PCr half-time was 45% longer in diabetic patients compared with controls (27.3 +/- 3.5 vs 18.7 +/- 0.9 s, p < 0.05), whereas IMCL content was similar (1.37 +/- 0.30 vs 1.25 +/- 0.22% of the water resonance), and insulin sensitivity was reduced in type 2 diabetes patients (26.0 +/- 2.2 vs 18.9 +/- 2.3 mumol min(-1) kg(-1), p < 0.05 [all mean +/- SEM]). PCr half-time correlated positively with fasting plasma glucose (r (2) = 0.42, p < 0.01) and HbA(1c) (r (2) = 0.48, p < 0.05) in diabetic patients. The finding that in vivo mitochondrial function is decreased in type 2 diabetes patients compared with controls whereas IMCL content is similar suggests that low mitochondrial function is more strongly associated with insulin resistance and type 2 diabetes than a high IMCL content per se. Whether low mitochondrial function is a cause or consequence of the disease remains to be investigated.